A common high-pressure metamorphic evolution of interlayered eclogites and metasediments from the ‘ultrahigh-pressure unit’ of the Tianshan metamorphic belt in China - Li, Jilei; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Song, Yun-Hui (Lithos, 2015)
Petrological and mineralogical data of interlayered eclogite, marble and quartz–mica schist from a drill core are used to constrain the metamorphic evolution of metavolcanics and intercalated metasediments in the Tianshan (ultra-)high-pressure/low-temperature [(U)HP/LT] metamorphic belt, NW China. The eclogite mainly consists of varying amounts of garnet, omphacite, quartz and zoisite, the marble of calcite (> 95 vol.%) with minor zoisite and phengite, and the schist of quartz and mica with minor calcite, chlorite, albite and garnet. Using garnet isopleth thermobarometry, pseudosection calculations for the eclogite and quartz–mica schist reveal a common metamorphic evolution under HP condition of both rock types that is also consistent with the temperature estimates for the marble using conventional thermometry. The uniform P–T paths of the interlayered eclogite and quartz–mica schist, as well as compatible temperature data of the marble, document that the whole rock suite constitutes a coherent HP unit during peak metamorphic conditions and exhumation. Thus protoliths of eclogite and associated sediments are believed to have undergone the same metamorphic evolution. In addition, the data gained by the present study of the HP rocks, which were collected in the northern part of the Chinese Tianshan (U)HP/LT belt, do not support the recently proposed tectonic scheme that this metamorphic terrane consists of a northern “coherent UHP unit” and a southern “coherent HP unit”.<br
Keywords: High pressure; Eclogite; Pseudosection; P–T evolution; Tianshan

Coexisting carbonate-bearing eclogite and blueschist in SW Tianshan, China: Petrology and phase equilibria. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (Journal of Asian Earth Sciences, 2012)
Carbonate-bearing eclogite and blueschist coexist in the same lithological sequence in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. Both of them consist of the mineral assemblage garnet+omphacite+dolomite±magnesite+phengite±paragonite+epidote/clinozoisite+glaucophane±barroisite/(Mg-)katophorite+rutile/titanite+pyrite. The eclogite has an omphacite content of ca. 43vol.% and a glaucophane content of <1vol.%. In contrast, the blueschist has an omphacite content of <8vol.% and a glaucophane content of ca. 43vol.%. The blueschist occurs as bands or interlayers in the eclogite. Lawsonite pseudomorphs of epidote/clinozoisite+paragonite assemblages in garnet are commonly observed in the eclogite and blueschist. High carbonate contents in oceanic metabasalts suggest that the precursor basaltic crust has undergone significant hydrothermal alteration prior to subduction. Mineral assemblages and textures show that the omphacite-carbonate-bearing blueschist and the carbonate-bearing eclogite underwent an identical metamorphic evolution. Phase equilibrium modeling in the TiNCaKFMASCHO system further indicates that both the carbonate-bearing eclogite and the omphacite-bearing blueschist equilibrated at peak metamorphic conditions of 540-565°C and 21.8-23.1kbar. Under these conditions calculated X CO2 isopleths reveal the presence of a mainly aqueous fluid phase (X CO20.02) for the coexisting eclogite and omphacite-bearing blueschist. The stability of the high-pressure mineral assemblages in the eclogite and the omphacite-bearing blueschist is due to differences of the respective bulk-rock composition (the CaO content in particular). This study suggests that three different kinds of blueschist were formed during subduction and exhumation of the South Tianshan oceanic crust, including prograde blueschist formed prior to eclogitization, retrograde blueschist formed by rehydration of eclogite during exhumation in the subduction channel, and coexisting blueschist with eclogite under peak metamorphic conditions. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.coexis
Keywords: Coexistence; Eclogite; Omphacite-bearing blueschist; Pseudosection; Tianshan (ultra-)high-pressure/low-temperature belt

Compositional zoning in dolomite from lawsonite-bearing eclogite (SW Tianshan, China): Evidence for prograde metamorphism during subduction of oceanic crust. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (American Mineralogist, 2014)
Dolomite with compositional zoning was discovered in carbonate-lawsonite- bearing eclogites in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. The eclogite-facies dolomite occurs as matrix porphyroblast and as inclusion in garnet, both of which display the same chemical zoning pattern. The dolomite contains inclusions of calcite (probably after aragonite), magnesite, glaucophane, lawsonite (and its pseudomorphs), allanite, epidote, paragonite, phengite, and omphacite. The chemical zoning in dolomite is well defined by a continuous core-to-rim Mg increase and Fe-Mn decrease. The concentrations of transition metal elements, REE, and Y also decrease from core to rim of the dolomite. Thermodynamic modeling demonstrates that the Fe-Mg zoning of dolomite is largely temperature dependent and, thus, is interpreted as prograde growth zoning, which developed during subduction of carbonate-bearing oceanic crust. It is suggested that dolomite in equilibrium with garnet formed as a result of changing matrix compositions due to increasing temperatures. In addition, thermodynamic modeling demonstrates that during subduction at high-pressure conditions prograde-formed aragonite and dolomite were transformed to dolomite and magnesite. Furthermore, Fe-rich magnesite inclusions in matrix dolomite and in dolomite inclusions in garnet are shown to have formed during high-pressure conditions prior to peak metamorphic conditions and, therefore caution is warranted using Fe-bearing magnesite occurrences in eclogite-facies rocks as an unambiguous ultrahigh pressure indicator as previously suggested. © 1997 - 2014 Mineralogical Society of America. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.compos_1
Keywords: Dolomite; Eclogite; High pressure; Magnesite; Prograde zoning; Tianshan

Final Assembly of the Southwestern Central Asian Orogenic Belt as Constrained by the Evolution of the South Tianshan Orogen: Links With Gondwana and Pangea - Wang, Xin-Shui; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Li, Jilei; Xue, Shengchao (Journal of Geophysical Research. Solid Earth, 2018)
The South Tianshan Orogen marks the final assembly of the southwestern Central Asian Orogenic Belt (CAOB) and the Karakum–Tarim cratons. Here we present an integrated mineralogical, geochemical, and geochronological study of the Wuwamen ophiolitic mélange in the South Tianshan to better understand the tectonic evolution of the western CAOB and its links to Gondwana and Pangea. Mantle peridotites with mineral compositions similar to those of abyssal peridotites and basalts with N‐MORB geochemical affinities suggest that the Wuwamen ophiolite was formed in a mid‐ocean ridge setting. Arc‐related gabbro and plagiogranite stocks intruding the mantle peridotites yielded zircon U–Pb ages of 441.1 ± 4.2 and 442.8 ± 2.4 Ma, indicating that the Wuwamen ophiolite got emplaced prior to 440 Ma. Sericite‐quartz schist from the ophiolitic mélange matrix with abundant 481–319 Ma detrital zircon grains is crosscut by a two‐mica granite dike with a zircon U–Pb age of 321.3 ± 1.7 Ma, thereby constraining the formation of the Wuwamen ophiolitic mélange at 320 Ma. In conjunction with published data, we propose that the South Tianshan Ocean opened in the late Neoproterozoic and promoted the subsequent separation of microcontinents in the western CAOB from the northeast Gondwana margin during Gondwana assembly. Furthermore, the closure of the South Tianshan Ocean led to the final assembly of the southwestern CAOB and the Karakum–Tarim cratons and their incorporation into Pangea at 320 Ma.<br
Keywords: Central Asian Orogenic Belt; Tianshan; Wuwamen ophiolite; Gondwana; Pangea

Fluid-mediated metal transport in subduction zones and its link to arc-related giant ore deposits: Constraints from a sulfide-bearing HP vein in lawsonite eclogite (Tianshan, China). - Li, Jilei; Gao, Jun; John, Timm; Klemd, Reiner; Su, Wen (Geochimica Et Cosmochimica Acta, 2013)
High-pressure (HP) veins in eclogites provide insight into element mobility during fluid-rock interaction in subduction zones. Here, we present a petrological-geochemical study of a sulfide-bearing HP vein and its massive lawsonite eclogite host rock from the Chinese Tianshan (ultra-)high-pressure/low-temperature metamorphic belt. The omphacite-dominated vein is enveloped by a garnet-poor, sulfide-bearing eclogite-facies reaction selvage. Lawsonite, garnet, omphacite, glaucophane and other HP minerals occur as inclusions in pyrite porphyroblasts of the selvage rock, indicating that the selvage formed prograde under eclogite-facies conditions. Relicts of wall-rock garnet (Grt_I) cores in recrystallized selvage garnet (Grt_II) close to the wall rock and the Ca distribution in Grt_II, which images the overgrown selvage matrix, indicate that the selvage formed due to dissolution-precipitation processes as a consequence of fluid-rock interaction of the wall rock eclogite with the vein-forming fluid. The peak metamorphic P-T conditions of the wall-rock eclogite are estimated at ca. 590. °C and 23. kbar. Mass-balance calculations indicate that the reaction selvage experienced: (1) a depletion of the large-ion lithophile elements (K-Rb-Ba) of up to 100% relative to their concentrations in the wall-rock eclogite; (2) a moderate depletion of the HREE and some transition metal elements including Fe, Cu, Ni, Zn, Co, Cr, and Mn (10-40%); (3) a significant enrichment of CaO (up to 50-80%), Sr (up to 200%), Pb (up to 170%) and S (up to 210%); (4) a slight to moderate enrichment of the LREE (10-20%) and MREE (0-40%); whereas (5) the HFSE show no significant variations.The chemical changes in the selvage suggest that the fluid, which caused the dissolution of the wall-rock and the precipitation of the selvage assemblage while the vein formed, was probably a mixture of an "internal" fluid derived from the prograde dehydration (e.g., lawsonite breakdown) of the wall rock and an "external" fluid most likely derived from dehydrating altered oceanic crust located in stratigraphically lower units of the subducting slab. The external fluid introduced Ca, S, Sr, Pb and at least parts of the LREE and the MREE into the selvage, whereas some elements, such as the remaining LREE and MREE, may have been derived from the wall rock eclogite via diffusional transport into the selvage. The enrichment of Ca and L-MREE is displayed by the abundant growth of selvage epidote. In contrast, the dissolution of garnet and phengite released significant amounts of HREE and LILE (K-Rb-Ba) into the passing fluid, because the chemical changes within the selvage prevented the formation of a mineral assemblage with sufficiently high bulk-fluid partition coefficients for these elements. Significant amounts of transitional metal elements were released into the fluid during the dissolution of white mica and the dissolution-precipitation behavior of garnet, omphacite, dolomite and sulfides. Thus the LILE and HREE along with some transition metal elements (e.g., Fe, Cu, Ni and Zn) were mobilized during the dissolution-precipitation processes that led to the selvage formation. Accordingly the slab fluids are not only strongly enriched in LILE and depleted in HFSE, but also carry significant amounts of transition metals. It is most likely that slab fluids strongly contribute to the metal flux into the arc magma systems finally resulting in giant arc-related ore deposits. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.fluidm

Large-scale porphyry-type mineralization in the Central Asian metallogenic domain: A review - Gao, Jun; Klemd, Reiner; Zhu, Mingtian; Wang, Xin-Shui; Li, Jilei; Wan, Bo; Xiao, Wenjiao; Zeng, Qingdong; Shen, Ping; Sun, Jinggui; Qin, Kezhang; Campos, Eduardo (Journal of Asian Earth Sciences, 2017)
A series of porphyry-type Cu-(Mo)-(Au) deposits including some giant world-class deposits such as Kounrad, Aktogai, Kal’makyr, Oyu Tolgoi and Chalukou occur in the Central Asian metallogenic domain (CAMD). The outline of the CAMD almost overlaps with that of the Central Asian orogenic belt (CAOB), which is located between the East Europe, Siberia, Tarim and North China cratons. The CAMD comprises sparsely exposed tectonic slices of Precambrian high-grade metamorphic basement rocks that are sandwiched between Phanerozoic accretionary complexes and arc rocks. According to geological, metallogenic, geochronological and tectonic setting characteristics, the CAMD comprises three metallogenic provinces: (1) the Kazakhstan Cu-Au-Mo, (2) the Mongolia Cu-Au and (3) the Northeast China Mo-Cu metallogenic provinces. Early Paleozoic (∼490 to 440 Ma) and Late Paleozoic (∼330 to 295 Ma) large scale porphyry-type mineralization in the Kazakhstan metallogenic province is intimately associated with the evolution of the Central Tianshan–Yili–Northern Tianshan–Kokchetav–Chingiz Paleozoic arc system which was terminated by the late Permian closure of the western segment of the Paleo-Asian Ocean. In contrast, the ∼370 Ma and ∼240 Ma porphyry-type mineralization of the Mongolia metallogenic province is related to the Tuva–Mongolia arc collage system that was formed during the evolution of the Paleo-Asian Ocean in the Paleozoic and the Mongol–Okhotsk Ocean in the early Mesozoic. Furthermore, the Northeast China metallogenic province was affected by three distinct geodynamic processes that were associated with the Paleo-Asian, Mongol–Okhotsk and Paleo-Pacific Oceans during the Paleozoic (>250 Ma), the early Mesozoic (>200 Ma) and the late Mesozoic (200–90 Ma), respectively. Except for the Early Paleozoic Cu mineralization at Duobaoshan (∼480 Ma) and Bainaimiao (440 Ma), the porphyry-type mineralization of this metallogenic province is predominantly characterized by widespread Mesozoic Mo mineralization. In general, porphyry-type deposits of the CAMD have geological, structural, metallogenic, alteration and fluid characteristics, which are consistent either with those related to the oceanic subductional arc settings of the Circum-Pacific metallogenic domain or with those of the continental collisional environment in the Tethyan metallogenic domain. The involvement of highly oxidized intermediate to felsic magmas is fundamental for the formation of porphyry deposits. Even though the prevalent MASH and slab melting models can be employed to interpret the genesis of some porphyry Cu deposits in the CAMD, a here newly suggested model, which is based on ‘pre-enriched mafic lower crust and the subduction of a relictic mid-oceanic ridge’, is thought to explain the large scale copper mineralization in the Balkhash–West Junggar metallogenic belt of the Kazakhstan metallogenic province. Nevertheless, most of the porphyritic suites associated with the Mo deposits in the Northeast China metallogenic province have relatively depleted mantle-like neodymium and hafnium isotopic compositions, suggesting that the ore-forming granitic magma may have predominantly been derived from juvenile lower crust. Upwelling of asthenosphere may have triggered the melting of the lower crust during post-collisional extension subsequent to the closure of the Paleo-Asian Ocean in the Triassic, the subduction of the Paleo-Pacific ocean in the Jurassic and the thinning of the lithosphere caused by rollback of the Paleo-Pacific plate in the Cretaceous. Ancient crustal components were only locally found to have been involved in the magma source of several medium-large Mo deposits.
Keywords: Porphyry-type deposits; Porphyry-type mineralization; Central Asian metallogenic domain; Central Asian Orogenic Belt

Metamorphic evolution of (ultra)-high-pressure subduction-related transient crust in the South Tianshan Orogen (Central Asian Orogenic Belt): Geodynamic implications - Klemd, Reiner; Gao, Jun; Li, Jilei; Meyer, Melanie (Gondwana Research, 2015)
The study of subduction-related high-pressure- and ultra-high-pressure metamorphic rocks exposed in orogenic belts is critical for unraveling the tectonothermal evolution of an orogen. The South Tianshan Orogen of the southwestern Central Asian Orogenic Belt, one of the world's largest accretionary orogens, contains several Paleozoic (ultra-)high-pressure ((U)HP) metamorphic terranes. (U)HP eclogites, blueschists and associated (U)HP metasedimentary rocks of continental and oceanic origin were reported from two localities in the Northern Tianshan (NTS) of Kazakhstanand Kyrgyzstan, namely from the Ordovician Aktyuz and Makbal metamorphic terranes. Furthermore Lower Carboniferous (U)HP eclogites and blueschists of oceanic origin are located in the Southern Tianshan Accretionary Complex (STAC) of southern Kyrgyzstan (Atbashi) and northwestern China (Akeyazi). The continentally-derived Aktyuz eclogite is considered to have experienced a continuous clockwise prograde P–T path with peak metamorphic conditions of ca. 1.6–2.1 GPa at 610–670 °C, corresponding to a burial depth of about 70 km. A peak metamorphic Lu–Hf garnet isochron age of 474 ± 2 Ma for the retrogressed eclogite of continental origin is in accordance with a Sm–Nd garnet isochron age of 462 ± 7 Ma interpreted as time of cooling and decompression of the metamorphic rock assemblage below 650 to 600 °C. Quantitative P–T pseudosection modeling for peripheral Makbal HP garnet amphibolites of continental origin also revealed a continuous clockwise P–T path with peak-metamorphic conditions of ca. 1.4 GPa at ca. 620 °C followed by an isothermal uplift to ca. 0.7 GPa. Furthermore, prograde P–T paths of oceanically-derived central Makbal high-pressure metabasic rocks revealed peak metamorphic conditions between 520 °C and 560 °C at 2.2 GPa to 2.5 GPa with subsequent isothermal decompressions. The metamorphic (P–T) evolution of a garnet–chloritoid–talc schist is exhibited by a P–T trajectory starting ca. 480 °C at 2.5 GPa, followed by peak pressures of ca. 2.85 GPa at 525 °C and peak temperatures of ca. 580 °C at 2.4 GPa. A Lu–Hf peak metamorphic age of 470.1 ± 2.5 Ma for a peripheral garnet amphibolite is in accordance with a garnet-growth Sm–Nd age of 475 ± 4 Ma of the UHP garnet–chloritoid–talc schist. Different and variable P–T paths show that former oceanic and continental crust at Makbal was subducted to different maximum depths (HP versus UHP conditions). The (U)HP metamorphism of oceanic and continental mafic rocks from the Aktyuz and Makbal metamorphic terranes is assumed to have occurred in a similar time frame of between 500 and 460 Ma. The proposed geodynamic model for the HP Aktyuz metamorphic terrane incorporates the deep northeast-directed subduction of NTS continental crust under the Ankrakhai block of Paleo-Kazakhstan subsequent to the closure of the Djalair–Naiman Basin. At Makbal the final consumption of the oceanic crust of the Terskey Ocean to the northeast was immediately followed by the deep subduction of a (thinned) passive continental margin of the Central Tianshan Arc Terrane (CTA). Both scenarios are in accordance with continental-type subduction geodynamics producing the subduction-related (U)HP rocks during continental–continental collision processes. The exhumation of detached oceanic material by channel flow may have been initiated by the transient subduction of oceanic and subsequent continental crust. The Lower Carboniferous (U)HP metamorphic terranes (Atbashi and Akeyazi) in the Southern Tianshan Accretionary Complex are mainly composed of metasediments which host some lenses and boudins of oceanically-derived blueschists and eclogites. Most eclogites, blueschists and metasediments have experienced peak high-pressure metamorphism (480–580 °C at 1.4–2.1 GPa), while some slices display UHP-conditions (2.7–3.3 GPa at 570–630 °C). Multi-point Lu–Hf and Sm–Nd isochrons from several eclogite and blueschist samples from the Atbashi and Akeyazi metamorphic terranes revealed consistent ages of ca. 320–315 Ma for the peak of metamorphism, thereby confirming that (U)HP metamorphism occurred during a single subduction event. The highly variable peak metamorphic conditions displayed by the (U)HP rocks imply that metamorphism of the metasediments and the various metabasic rocks occurred in different depths of the subduction zone. (U)HP metabasites and metasediments exhibit different P–T paths, which is consistent with the chaotic incorporation in a subduction channel resulting in the eventual exhumation as a mélange. This scenario is much in agreement with initial subduction of oceanic crust and accretionary wedge sediment removal by subduction erosion and thus is similar to accretionary-type subduction terranes, although, with higher peak P–T conditions than previously recorded. The absence of significant melting, in combination with the variable peak pressure metamorphic conditions and the intimate interlayering of high- and ultrahigh-pressure rocks, suggests that the (U)HP rocks were derived from varying depths within the subduction zone and then juxtaposed during exhumation in the subduction channel. This is in accordance with exhumation of the (U)HP rocks by channel flo
Keywords: South Tianshan Orogen; (Ultra-)high-pressure metamorphism; Geochronology; Accretionary- and continental-type subductions; Channel flow exhumation

Poly-cyclic Metamorphic Evolution of Eclogite: Evidence for Multistage Burial–Exhumation Cycling in a Subduction Channel - Li, Jilei; Klemd, Reiner; Gao, Jun; John, Timm (Journal of Petrology, 2016)
(Ultra-)high-pressure [(U)HP] eclogites provide direct evidence for metamorphic processes at mantle depths in subduction zones. Textural evidence and pressure–temperature ( P – T ) path reconstruction allow a unique opportunity to constrain the geodynamic processes along the plate interface. To better understand the dynamics of subduction channels, we present a detailed petrographical, petrological and pseudosection modeling study of a metamorphically complex HP eclogite sample from a tectonic block of the Akeyazi (U)HP metamorphic terrane in the Chinese Tianshan. Mineral chemical variations and textural discontinuities show that all the major phases of the rock (garnet, epidote, clinopyroxene and amphibole) display multiple growth zones compatible with a poly-cyclic evolution including two burial–exhumation cycles. The precise P – T path derived from thermodynamic modeling based on effective bulk compositions suggests that the eclogite underwent complex burial–exhumation cycles with two P – Tloops indicated by the occurrence of polyphase garnet and mutually replaced and regrown amphibole. It is suggested that the eclogite sample, which represents a relic of tectonically detached oceanic crust, underwent two burial–exhumation cycles during convective flow in a subduction channel. This natural occurrence is consistent with numerical simulation studies showing that pressure cycling is to be expected for deeply subducted oceanic crust in a subduction channel. The modeled exhumation process for the eclogite sample corresponds to a previously suggested subduction channel exhumation model for the Akeyazi (U)HP rocks.<br
Keywords: subduction channel; Chinese Tianshan; eclogite; poly-cyclic metamorphism; polyphase mineral growth; pseudosection; P–T path

Redox processes in subducting oceanic crust recorded by sulfide-bearing high-pressure rocks and veins (SW Tianshan, China) - Li, Jilei; Gao, Jun; Klemd, Reiner; John, Timm; Wang, Xin-Shui (Contributions To Mineralogy and Petrology, 2016)
The oxidized nature of the sub-arc mantle and hence arc magmas is generally interpreted as a result of the migration of subduction-related oxidizing fluids or melts from the descending slab into the mantle wedge. This is of particular importance seeing that the oxidization state of sub-arc magmas seems to play a key role in the formations of arc-related ore deposits. However, direct constraints on the redox state of subducted oceanic crust are sparse. Here, we provide a detailed petrological investigation on sulfide- and oxide-bearing eclogites, blueschists, micaschists, eclogite-facies and retrograde veins from the Akeyazi high-pressure (HP) terrane (NW China) in order to gain insight into the redox processes recorded in a subducting oceanic slab. Sulfides in these rocks are mainly pyrite and minor pyrrhotite, chalcopyrite, bornite, molybdenite, sphalerite and chalcocite, including exsolution textures of bornite–chalcopyrite intergrowth. Magnetite, ilmenite and pyrite occur as inclusions in garnet, whereas sulfides are dominant in the matrix. Large pyrite grains in the matrix contain inclusions of garnet, omphacite and other HP index minerals. However, magnetite replacing pyrite textures are commonly observed in the retrograded samples. The eclogite-facies and retrograde veins display two fluid events, which are characterized by an early sulfide-bearing and a later magnetite-bearing mineral assemblage, respectively. Textural and petrological evidences show that the sulfides were mainly formed during HP metamorphism. Mineral assemblage transitions reveal that the relative oxygen fugacity of subducted oceanic crust decreases slightly with increasing depths. However, according to oxygen mass balance calculations, based on the oxygen molar quantities (nO2), the redox conditions remain constant during HP metamorphism. At shallow levels (<60 km) in the subduction channel, interaction with oxidized fluid seems to have caused an increase of the oxygen fugacity and the oxidation state of exhuming HP rocks. This study suggests that oxygen components are not released in significant amounts during HP metamorphism of subducted oceanic crust and, thus, cannot be responsible for oxidizing the mantle wedge and increasing the oxidation state of sub-arc mantle melts.<br
Keywords: Subducted oceanic crust; Fluids; Oxygen fugacity; Eclogite; Sulfides; Magnetite

Subduction channel fluid–rock interaction and mass transfer: Constraints from a retrograde vein in blueschist (SW Tianshan, China) - Li, Jilei; John, Timm; Gao, Jun; Klemd, Reiner; Wang, Xin-Shui (Chemical Geology, 2017)
One widely neglected part of the subduction zone fluid cycle is the retrograde fluid flow along the plate interface. This fluid flow may facilitate the exhumation of slab-derived rocks within the subduction channel. However, our understanding on the nature and behavior of these retrograde fluids is still insufficient. Retrograde veins preserved in HP–UHP rocks can provide valuable information about fluid activities and mass transfer at the plate interface and exhumation processes. In this study, we present a petrological and geochemical investigation of a typical retrograde vein and its blueschist host rock, which occurs throughout the whole Akeyazi (U)HP terrane in the Chinese southwestern Tianshan. The magnetite-bearing albite–calcite vein, representing an external fluid pathway, crosscuts the host blueschist that mainly consists of glaucophane, garnet, epidote and titanite. Along the fluid conduit the immediate wall-rock experienced greenschist-facies overprinting as displayed by an albite-rich selvage that grades into a chlorite–biotite selvage towards the host rock. The replacements of garnet by chlorite and glaucophane by albite are thought to have occurred due to an interface-coupled dissolution-precipitation mechanism. Mass balance calculations show that during fluid–rock interaction large amounts of LILE (K–Rb–Ba–Cs and Pb), Cu and CO2 were added to the selvages (mass gain > 200%), whereas the altered wall-rock released significant amounts of Ca, Li, Sr, REE and transition metal elements (V–Mn–Co–Ni–Zn) (mass loss mainly between 40 and 100%) due to the dissolution of glaucophane, garnet and epidote. The chlorite–biotite selvage experienced additional SiO2 and Na2O mass losses as well as FeO, MgO and H2O mass gains, whereas the albite-rich selvage underwent exactly the opposite mass transfer with respect to these components. The Al, Ti, Nb, Ta and Cr contents were constant during the alteration. Therefore, the retrograde fluid causing greenschist-facies overprinting of the blueschist host in the subduction channel (at ca. 30 km depth) is proposed to be oxidized and enriched in LILE, Cu and CO2components, whereas Ca, Li, Sr, REE, Y and transition metal elements (V–Mn–Co–Ni–Zn) are thought to have been mobilized during fluid-rock interaction. In addition, the main fluid sources (sediments, oceanic crust or serpentinites) diversely contribute to retrograde fluids at different depths in the subduction channel.<br
Keywords: Element mobility; Fluid–rock interaction; Retrograde fluid flow; Albite vein; Blueschist; Tianshan

The Central Tianshan Block: A microcontinent with a Neoarchean-Paleoproterozoic basement in the southwestern Central Asian Orogenic Belt - Wang, Xin-Shui; Gao, Jun; Klemd, Reiner; Jiang, Tuo; Li, Jilei; Zhang, Xi; Xue, Shengchao (Precambrian Research, 2017)
The Central Tianshan Block (CTB) is one of the major continental constituents of the western Central Asian Orogenic Belt (CAOB). Its nature and origin is essential for understanding the accretionary processes and the reconstruction of the architectural framework of the CAOB. The Wuwamen Metamorphic Complex (WMC), which is believed to represent the basement of the CTB, was incorporated into the Wuwamen ophiolitic mélange during the Paleozoic evolution of the South Tianshan Ocean. The WMC is mainly composed of amphibolite-facies volcano-sedimentary rocks, including migmatites, orthogneisses, amphibolites, schists and locally marbles. Zircon U–Pb geochronology suggests that the protoliths of the interlayered biotite-two feldspar and biotite-plagioclase-hornblende gneisses in the Yangjuan area were formed between 2529 and 2513 Ma and overprinted by amphibolite-facies metamorphism between 1815 and 1809 Ma. Subsequently, the gneisses were intruded by ∼1724 Ma meta-mafic dykes and ∼787 Ma leucogranite dykes/veins. Geochemical data reveal that the biotite-two feldspar gneisses have high-silica adakite affinities with high SiO2 and Na2O contents as well as high Sr/Y ratios (61–117) and slightly evolved zircon Hf isotopic compositions. Consequently, they are interpreted to be the products of partial melting of relatively old subducted oceanic crust. In contrast, the interlayered biotite-plagioclase-hornblende gneisses have high MgO, Cr, Co and Ni contents and prominent negative Nb–Ta–Ti anomalies, indicating derivation from partial melting of an ancient sub-continental lithospheric mantle in a continental arc setting. The ∼1.72 Ga meta-mafic dykes have geochemical similarities of typical Fe-Ti basalts and are characterized by incompatible element enrichments and primitive Sr–Nd–Hf isotopic signatures ((87Sr/86Sr)i = 0.703446 − 0.703535); ɛNd(t) = +6.49 to +6.90; zircon ɛHf(t) = +0.57 to +10.6), which is consistent with partial melting of a relatively fertile, isotopically depleted asthenospheric mantle in a post-collisional extensional setting. In addition, the ∼787 Ma leucogranites are trondhjemitic in composition and display extremely low total REE contents and highly evolved Nd–Hf isotopic signatures (ɛNd(t) = −4.71 to −4.53; zircon ɛHf(t) = −19.4 to −13.0). They are thought to have no petrogenetic relationship with the host orthogneisses and to be products of a foreign melt injection. Our new data provide robust evidence for a Neoarchean–Paleoproterozoic basement of the CTB. Comparison of the tectono-thermal-magmatic events reveals that the CTB and the Tarim Craton have a partly overlapping Precambrian crustal evolution, and thus the CTB could have originated from the Tarim Craton. However, a major difference between both is the presence of juvenile Mesoproterozoic magmatism in the CTB and its absence in the Tarim Craton and, therefore, further geological and geochronological research is required to determine the precise origin of the CTB and its tectonic affinity with adjacent terranes in the western CAOB.<br
Keywords: Central Tianshan Block; Crustal evolution; Precambrian basement; Tarim Craton; Central Asian Orogenic Belt